Malaria Altering Host Attractiveness and Mosquito Feeding. Issue 5 (May 2017) - Cator, Lauren
Abstract : Several studies have suggested that malaria parasites stack the odds of transmission in their favour by manipulating the attraction profiles of their hosts. A recent study provides evidence that a specific parasite factor, ( E )-4-hydroxy-3-methyl-but-2-enyl pyrophosphate, may increase both the attractiveness of infected vertebrates and the susceptibility of mosquitoes to infection.